Leitura sócio interativa em língua inglesa: uma proposta metodológica de ensino à luz da Linguística Aplicada - GÓIS, Samara Oliveira de (2019)
This study deals with the reading ability of English as a Foreign Language in the perspective of teaching high school classrooms of a public school in São Luís. The general objective of the research was to check in what ways a Pedagogical Guidance Book as a methodological proposal and practical application of didactic sequences, containing textual genres and reading strategies could be efficient. The work initially started from a bibliographical study, raising some relevant historical facts about the teaching of languages in Brazil and contextualizing the choice of teaching (or not) foreign languages, especially English, according to the interests and political decisions of each historical moment. Excerpts from official documents referring to Brazilian educational policies, LDB (1996), PCN (2000) and Basil (2017) were also used as reference of what has been established and the focus on the development of language reading skill as a priority in Basic Education. Then, some conceptions of reading in English language and its mechanisms were defined, starting from Applied Linguistics and taking as assumptions the ideas of Almeida Filho (1999; 2013), Brown (1994), Lima Júnior (2016), Moita Lopes (1996) and Oliveira (2014; 2015) mainly. To develop this research, we have started from the following question: In what way can the application of a didactic sequence with reading strategies in a social interactionist perspective help in the teaching and learning of English language? To its materialization, we used as methodology some aspects of an action research, from pedagogical intervention type, in a quantitative and qualitative approach. The sample of participating subjects consisted of an English teacher and two groups of Senior high school students from a public school in Maranhão. The data collection instruments were: participant observation, observation form, semi-structured interviews and the application of two mixed questionnaires (diagnosis and post-intervention). The representative forms of data analysis were percentage numbers represented in quantitative graphs, and in the qualitative part, we use semantic content analysis according to Bardin (2016). The obtained results allow to conclude that the elaborated methodological proposition and the application of the didactic sequences were a significant experience to the research participants, encouraging their reflection and the beginning of a change of conception about the traditional process of reading in English language.